An investigation of risk factors for fracture in patients with osteoporosis and osteopaenia using biomechanical, biochemical and radiological assessments - Browne, Joseph (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
Osteoporosis is defined as a skeletal disorder characterised by compromised bone strength resulting in an increased risk for fracture. Hip fractures are the most common osteoporotic fracture in older adults and occur due to reduced bone strength and a propensity to falling. Dual X-ray absorptiometry (DXA) is the standard test to assess for osteoporosis in fracture patients, although there is a significant overlap between patients diagnosed with nornial and osteoporotic bones who subsequently fracture.
Keywords: Bioengineering, M.D.; M.D. Trinity College Dublin